Building and road machines with heat recovery of kinetic energy - B. N. Stickhanovskiy; L. M. Stickhanovskaya (Вестник СибАДИ, 2017)
In the article the question of the need to use in the construction and road vehicles used for the destruction of solids and frozen ground, the kinetic energy storage. Application of the kinetic energy storage principle in a big way during the working body acceleration to the protection of the machine body from knocks gives a number of advantages over machines with other methods of energy storage. Their main nih expansion of the upper limit of the striker speed range up to several hundred meters per second, the increase in energy density per unit weight of the machine, which significantly reduces the energy consumption of processes, the ability to smooth speed control, reduction of weight and dimensions. An example of copra testing for pins with high impact energy to disperse them in a large angular path.